Upton Sinclair : the Lithuanian Jungle : upon the centenary of The Jungle (1905 and 1906) by Upton Sinclair - Subačius, Giedrius (On the boundary of two worlds ;, 2006)
In his legendary novel The Jungle (1905 and 1906), Upton Sinclair included a conspicuous number of Lithuanian words, phrases and surnames. This volume is the first attempt to analyze aspects of Lithuanian linguistic and historical data from The Jungle . Sinclair discovered the Lithuanian language in Chicago and explored it with pleasure. He even confessed to having sang in Lithuanian. If you look for "a Lithuanian linguist" working in field-research conditions in Chicago's Back of the Yards--there is Upton Sinclair! The book targets Sinclair's motives for choosing Lithuanian characters, his sou.